Globalization, Citizenship, and Subjectivity in Self Construction - Poudel, Namita (Molung Educational Frontier, 2020)
One of the profound questions that troubled many philosophers is– “Who am I?” where do I come from? ‘Why am I, where I am? Or “How I see myself?” and maybe more technically -What is my subjectivity? How my subjectivity is formed and transformed? My attempt, in this paper, is to look at “I”, and see how it got shaped. To understand self, this paper tries to show, how subjectivity got transformed or persisted over five generations with changing social structure and institutions. In other words, I am trying to explore self-identity. I have analyzed changing subjectivity patterns of family, and its connection with globalization. Moreover, the research tries to show the role of the Meta field in search of subjectivity based on the following research questions; how my ancestor’s subjectivity changed with social fields? Which power forced them to change their citizenship? And how my identity is shaped within the metafield? The methodology of my study is qualitative. Faced to face interview is taken with the oldest member of family and relatives. The finding of my research is the subjectivity of Namita Poudel (Me) is shaped by the meta field, my position, and practices in the social field.